Annual (2023) taxonomic update of RNA-directed RNA polymerase-encoding negative-sense RNA viruses (realm Riboviria: kingdom Orthornavirae: phylum Negarnaviricota) - Kuhn, Jens H; Abe, Junya; Adkins, Scott; Alkhovsky, Sergey V; Avšič-Županc, Tatjana; Ayllón, María A; Bahl, Justin; Balkema-Buschmann, Anne; Ballinger, Matthew J; Kumar Baranwal, Virendra; Beer, Martin; Bejerman, Nicolas; et al. (The Journal of general virology, 2023)
In April 2023, following the annual International Committee on Taxonomy of Viruses (ICTV) ratification vote on newly proposed taxa, the phylum Negarnaviricota was amended and emended. The phylum was expanded by one new family, 14 new genera, and 140 new species. Two genera and 538 species were renamed. One species was moved, and four were abolished. This article presents the updated taxonomy of Negarnaviricota as now accepted by the ICTV.
Keywords: Phasmaviridae; Muvirales; Mymonaviridae; Artoviridae; Mononegavirales; Discoviridae; Tosoviridae; mononegaviral; RNA-viry; bunyavirus; Nyamiviridae; Phenuiviridae; Tulasviridae; virus nomenclature; Orthomyxoviridae; Negative-Sense RNA Viruses; Pneumoviridae; Serpentovirales; goujianviral; Tospoviridae; negarnaviricot; Bornaviridae; International Committee on Taxonomy of Viruses; Articulavirales; muviral; megataxonomy; RNA-Dependent RNA Polymerase; bunyaviral; Sunviridae; Aspiviridae; Riboviria; Fimoviridae; RNA-dependentní RNA-polymerasa; virus classification; megaclassification; Aliusviridae; Filoviridae; Negarnaviricota; articulaviral; Crepuscuviridae; virus taxonomy; Rhabdoviridae; RNA Viruses; Jingchuvirales; Paramyxoviridae; Orthornavirae; Myriaviridae; Lispiviridae; negativní RNA-viry; Nairoviridae; ICTV; Bunyavirales; Arenaviridae; Peribunyaviridae; Natareviridae; Hantaviridae; Goujianvirales; Tenuivirus; serpentoviral